The truth about hippos - Eaton, Maxwell, III (Roaring Brook Press, 2018)
"Did you know that there are two types of hippo: the common hippo and the pygmy hippo (which is like a common hippo but smaller)? Did you know that all hippos live in Africa? Did you know that hippos can't actually swim?"--Jacket.